2021
DOI: 10.5582/bst.2021.01061
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine research focusses on safety, efficacy, immunoinformatics, and vaccine production and delivery: a bibliometric analysis based on VOSviewer

Abstract: Coronavirus Disease 2019 , caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has affected tens of millions of people globally since it was declared a pandemic by the World Health Organization (WHO) on March 11, 2020. There is an urgent need for safe and effective preventive vaccines to curb this pandemic. A growing amount of related research has been published. This study aimed to provide the current status of COVID-19 vaccine using bibliometric analysis. We searched Embase.com and ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…This study had some limitations. Although this study is an anonymous survey, there is still a gap between it and the fact that vaccination is under real conditions ( 31 , 32 ). The subjects of this study were mainly from east China and are not representative of the country as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…This study had some limitations. Although this study is an anonymous survey, there is still a gap between it and the fact that vaccination is under real conditions ( 31 , 32 ). The subjects of this study were mainly from east China and are not representative of the country as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometric and scientometric analyses have been conducted to explore the emerging research focuses related to COVID-19. Such research focuses identified by researchers in mid-high-income countries include available treatment options, such as approved drugs or vaccines, or candidate management strategies [ 9 , 10 , 11 ]. While some bibliometric papers focus on summarizing research foci, other scientometric publications have assessed the scholarly output of researchers mainly from countries in Asia, America or Europe [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their analysis recoursed to immunoinformatics and advocated a sequence analysis of the pathogenic strains of SARS‐CoV‐2 to design vaccine candidates. These vaccine candidates may provide meaningful, timely directives for an effective vaccine against SARS‐CoV‐2 (Chen et al, 2021 ; Kumar et al, 2021 ; Oyarzun et al, 2021 ). Moreover, SARS‐CoV‐2 spike glycoprotein followed by epitopes' use in constructing a multi‐epitope peptide vaccine construct (MEPVC) is also an attractive candidate for a vaccine, antibodies, and inhibitor development because of the many roles it plays in attachment, fusion, and entry into the host cell.…”
Section: State Of the Art And Problem Statementmentioning
confidence: 99%